Hand Hygiene Compliance in Pediatric Emergency of a Lower-Middle Income Country: A Quality Improvement Study - Angurana, Suresh Kumar; Chetal, Pooja; Mehta, Richa; Suthar, Renu; Sundaram, Venkataseshan; Singh, Ranjana; Kaur, Rupinder; Kaur, Harinder; Biswal, Manisha; Kumar, Praveen; Jayashree, Muralidharan (Frontiers in Pediatrics, 2022)
Background Prospective data on hand hygiene compliance in pediatric emergency department (PED) settings is limited. We studied the impact of quality improvement measures on the overall and health care personnel wise hand hygiene compliance rates in a busy PED. Methods The baseline hand hygiene compliance rates were audited from May–July 2018. The quality improvement interventions included various structural changes to the environment, administrative changes, education and training. During the interventions, auditing was continued for 2 months (August – September 2018). Statistical Process control charts were created. Results We observed a significant increase in overall compliance rates from 31.8 to 53.9% (p < 0.001). These improvements were observed in the children (29.6 to 46.4%, p < 0.001) as well as neonatal area (35.7% to 59.7, p < 0.001) of PED as well as amongst various health care personnel and in four out of the five moments of hand hygiene. Conclusion Hand hygiene compliance improved significantly in a busy PED of a lower middle-income country following quality improvement interventions. Such improvement was observed amongst all categories of health care personnel and different types of hand hygiene opportunities. This study demonstrates the feasibility and efficacy of simple quality improvement interventions in a challenging hospital environment.